2021
DOI: 10.15621/ijphy/2021/v8i4/1093
|View full text |Cite
|
Sign up to set email alerts
|

Predict Anterior Cruciate Ligament Injury In Elite Male Soccer Players? Focus On The Five Factors Maximum Model

Abstract: Background: For years, the rupture of the anterior cruciate ligament (ACL) has been a feared injury in young soccer players since it causes physiological and psychological changes while incurring significant economic losses. Methods: Through clinical research, understanding the mechanisms and identifying risk factors has enabled sports and performance professionals to establish robust models to predict and reduce the risk of ACL injury. Developments in medical devices also allow a more precise, more objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Of the various RTS tests described to assess safe RTS after ACLR, recent literature has identified some biomechanical variables associated with secondary ACL injury [89,100], with some literature suggesting RTS testing batteries should utilize a maximum of five variables/tests (e. g., strength/power, movement biomechanics, proprioception, kinesthesia, and balance) when synthesizing information regarding safe RTS after ACLR [101,102]. In a small prospective cohort study, Paterno et al [100] reported that during a drop vertical jump maneuver, biomechanical variables related to net hip rotation moment impulse, frontal plane knee range of motion during landing, asymmetries in sagittal plane knee moments at initial contact, and postural stability were collectively a strong predictor (i. e., sensitivity, 0.92; specificity, 0.88) of a contralateral or secondary ipsilateral ACL injury after primary ACLR.…”
Section: Objective Performance Testing and Rts After Aclrmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the various RTS tests described to assess safe RTS after ACLR, recent literature has identified some biomechanical variables associated with secondary ACL injury [89,100], with some literature suggesting RTS testing batteries should utilize a maximum of five variables/tests (e. g., strength/power, movement biomechanics, proprioception, kinesthesia, and balance) when synthesizing information regarding safe RTS after ACLR [101,102]. In a small prospective cohort study, Paterno et al [100] reported that during a drop vertical jump maneuver, biomechanical variables related to net hip rotation moment impulse, frontal plane knee range of motion during landing, asymmetries in sagittal plane knee moments at initial contact, and postural stability were collectively a strong predictor (i. e., sensitivity, 0.92; specificity, 0.88) of a contralateral or secondary ipsilateral ACL injury after primary ACLR.…”
Section: Objective Performance Testing and Rts After Aclrmentioning
confidence: 99%
“…However, current RTS criteria may not be valid for predicting safe RTS 28 30 95 , and more sophisticated biomechanical testing of known risk factors for ACL re-injury may be needed to more specifically synthesize information regarding safe RTS after ACLR ( Fig. 2 ) 77 78 79 86 88 89 101 102 .…”
Section: Introductionmentioning
confidence: 99%